2006
DOI: 10.1159/000093671
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Removal of High- and Low-Molecular-Weight Compounds in Hemodiafiltration with On-Line Regeneration of Ultrafiltrate

Abstract: Background: Current methods of renal replacement therapy, combining convection and diffusion, are largely unsatisfactory in removing uremic toxins. Adsorption is a third mechanism that has been applied in extracorporeal therapy. This study evaluates the impact of hemodiafiltration with on-line regeneration of ultrafiltrate, a new two-step integrated sorbent system, on in vivo removal of a wide spectrum of solutes with different molecular weights. Methods: Pre- and post-dialysis concentrations of small, medium-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 46 publications
0
26
0
1
Order By: Relevance
“…It is generally accepted that hemodiafiltration offers a highly effective dialysis modality that widens the spectrum of uremic toxins removed from small to medium-sized molecular solutes (18 -20). On-line hemodiafiltration using high-substitution fluid produces a greater clearance of large uramic toxins (21,22). Furthermore, we have reported that dialysis modalities with high convective transport are capable of reducing but not normalizing the percentage of CD14 ϩ CD16 ϩ monocytes (13).…”
Section: Discussionmentioning
confidence: 98%
“…It is generally accepted that hemodiafiltration offers a highly effective dialysis modality that widens the spectrum of uremic toxins removed from small to medium-sized molecular solutes (18 -20). On-line hemodiafiltration using high-substitution fluid produces a greater clearance of large uramic toxins (21,22). Furthermore, we have reported that dialysis modalities with high convective transport are capable of reducing but not normalizing the percentage of CD14 ϩ CD16 ϩ monocytes (13).…”
Section: Discussionmentioning
confidence: 98%
“…Although there is limited evidence about the range of cystatin C concentration during hemodialysis therapy, the levels before dialysis are in agreement with those measured by other authors and significantly higher post-dialysis than pre-dialysis. [17,20] This increase can be attributed to the low-flux membranes used, which retain cystatin C and other middle molecular weight molecules, in contrast to high-flux hemodialyzers or hemodiafiltration, which allow the removal of the above compounds and result in a substantial decrease in the post-dialysis levels of cystatin C. [21,22] We intended to determine if the increased concentration of serum cystatin C in hemodialysis patients is connected to the inflammatory factor CRP as well as to markers of atherosclerosis. As has been previously reported, the inflammatory process is related to atherosclerosis in chronic kidney disease [23,24] and is revealed by a release of CRP and inflammatory cytokines (i.e., Il-6) secreted by inflammatory cells present in atherosclerotic lesions [14,25] and also by leukocytes in contact with dialysis membranes.…”
Section: Discussionmentioning
confidence: 99%
“…22,31 The highest mass concentration was detected for the acute phase macromolecule a1-acid glycoprotein. 54 Most frequently reported concentrations concerned b2-microglobulin, indoxyl sulfate, homocysteine, uric acid, and parathyroid hormone (PTH). There were large variations in binding of protein-bound solutes.…”
Section: Overview Of Uremic Toxin Researchmentioning
confidence: 99%